Nurses’ tasks of monitoring the pain in patients with traumatic, infected wounds, based on cases studies - Szumska, Anna (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2017)
Pain as a subjective, unpleasant sensory and emotional experience is considered by the American Association for the Study of Pain as the fifth vital sign. The monitoring of this vital sign is one of the nurse’s responsibilities. The aim of this discourse is to portray nurses’ tasks in monitoring pain on the grounds of the estimation of subjective pain felt by patients with traumatic, infected wounds based on case studies. Our medical centre hospitalises patients with infected wounds, including post-injury wounds. Assessing the patient’s pain is an integral part of therapy. Defined, professional, constant activities towards providing the patient with the highest quality of medical care may be included in nurses’ tasks of monitoring the pain in hospitalised patients with traumatic, infected wounds.